Self-protective behavior and violent victimization - Santana, Shannon A. (Criminal justice Recent scholarship, 2007)
The importance of studying self-protective behaviors -- Prior research on self-protective behaviors -- Using the national crime victimization survey -- The effectiveness of self-protective behavior -- Past, present, and future research